2018
DOI: 10.1038/s41598-018-21088-4
|View full text |Cite
|
Sign up to set email alerts
|

A new high-resolution 3-D quantitative method for analysing small morphological features: an example using a Cambrian trilobite

Abstract: Taphonomic processes play an important role in the preservation of small morphological features such as granulation or pits. However, the assessment of these features may face the issue of the small size of the specimens and, sometimes, the destructiveness of these analyses, which makes impossible carrying them out in singular specimen, such as holotypes or lectotypes. This paper takes a new approach to analysing small-morphological features, by using an optical surface roughness (OSR) meter to create a high-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…These findings suggest that, in compacted material, the presence and/or depth of some transverse or longitudinal glabellar furrows should be considered more reliable for taxonomic identification than the presence and/or depth of others. Zhao et al (2008) and Esteve et al (2017Esteve et al ( , 2018 asserted that Oryctocephalus reticulatus (Lermontova, 1940;see Sundberg et al, 2011) and Oryctocephalus americanus Sundberg and McCollum, 2003b are synonymous with Oryctocephalus indicus, which is the index fossil for the Wuliuan Stage, Miaolingian Series (Zhao et al, 2019). All three species are very similar in cranidial shape (see Esteve et al, 2017) but differ in the number of transglabellar furrows, with only one furrow in O. reticulatus and O. americanus and three in O. indicus.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that, in compacted material, the presence and/or depth of some transverse or longitudinal glabellar furrows should be considered more reliable for taxonomic identification than the presence and/or depth of others. Zhao et al (2008) and Esteve et al (2017Esteve et al ( , 2018 asserted that Oryctocephalus reticulatus (Lermontova, 1940;see Sundberg et al, 2011) and Oryctocephalus americanus Sundberg and McCollum, 2003b are synonymous with Oryctocephalus indicus, which is the index fossil for the Wuliuan Stage, Miaolingian Series (Zhao et al, 2019). All three species are very similar in cranidial shape (see Esteve et al, 2017) but differ in the number of transglabellar furrows, with only one furrow in O. reticulatus and O. americanus and three in O. indicus.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…All three species are very similar in cranidial shape (see Esteve et al, 2017) but differ in the number of transglabellar furrows, with only one furrow in O. reticulatus and O. americanus and three in O. indicus. Zhao et al (2015) and Esteve et al (2017Esteve et al ( , 2018 suggested that this might be the result of taphonomy or biological variation. The study of compaction in Oryctocephalites palmeri described herein suggests that the differences in the number of transglabellar furrows in Oryctocephalus is reliable and synonymy of the three species of Oryctocephalus is doubtful.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…Fort et al 2012;Vazquez-Calvo et al 2012) and only more recently on geological heritage (e.g. Esteve et al 2018). However, to this day, they have not been used in geomorphological analysis nor in the valorisation of geoheritage.…”
Section: Contribution Of Micromorphometry To the Study Of Bedrock Rivmentioning
confidence: 99%
“…Taphonomical analyses of the archaeological findings: a process in which the materials unearthed in the site are studied to know the processes they suffered [32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%